IL-1 Receptor Antagonist Inhibits Early Granulation Formation. (April 2016) - Nicolli, Elizabeth A.; Ghosh, Ankona; Haft, Sunny; Frank, Renee; Saunders, Cecil James; Cohen, Noam; Mirza, Natasha
Purpose: Using a functional model of airway granulation tissue in laryngotracheal stenosis, we investigated changes in histopathology and inflammatory markers within granulation tissue in response to an interleukin-1 receptor antagonist (IL-1Ra). This study allows us to further delineate the immune response to wound healing and potentially identify treatment markers. Methods: Laryngotracheal complexes (LTCs) of donor mice underwent direct airway injury. The LTCs were transplanted into subcutaneous tissue of recipient mice in 2 groups: IL-1Ra treated and untreated. The IL-1Ra–treated arm received daily intraperitoneal injections of IL-1Ra for 3 weeks. The LTCs were then harvested. Granulation formation was measured. The mRNA expression of transforming growth factor (TGF) beta and IL-1 was quantified using real-time reverse transcript polymerase chain reaction. Results: There were statistically significant differences in lamina propria thickness. There were no statistically significant changes in mRNA expression of TGF-β and IL-1β between the treated and untreated specimens. Conclusions: Using a previously described murine model, we delineate inflammatory markers that can be targeted for potential therapy. While the levels of inflammatory markers do not change significantly, the lamina propria thickness shows that the effects of IL-1 have been inhibited. The early use of the IL-1Ra will inhibit the efficacy of IL-1 in the inflammatory cascade and can prevent early granulation formation.